acNASH index to diagnose nonalcoholic steatohepatitis: a prospective derivation and global validation study - YILMAZ, YUSUF (ELSEVIER, 2021)
Background: There is an unmet need for non-invasive biomarkers for the diagnosis of nonalcoholic steatohe-patitis (NASH) in non-specialized settings. We aimed to develop and validate a non-invasive test for diagnos -ing NASH in individuals with biopsy-proven nonalcoholic fatty liver disease (NAFLD). Methods: We developed a non-invasive test named the acNASH index that combines serum creatinine and aspartate aminotransferase levels in a derivation cohort of 390 Chinese NAFLD patients admitted to the hepa-tology center of the First Affiliated Hospital of Wenzhou Medical University (China) between December 2016 and September 2019 and subsequently validated in five external cohorts of different ethnicities of patients with biopsy-confirmed NAFLD (pooled n=1,089). Findings: The performance of the acNASH index for identifying NASH (defined as NAFLD activity score >5 with score of >1 for each steatosis, lobular inflammation and ballooning) was good in the derivation cohort with an area under receiver operating characteristics (AUROC) of 0.818 (95%CI 0.777-0.860). A cutoff of acNASH index <4.15 gave a sensitivity (Se) of 91%, a specificity (Sp) of 48% anda negative predictive value (NPV) of 83% for ruling-out NASH, con-versely, a cutoff of acNASH >7.73 gave a Sp of 91%, Se of 53% anda positive predictive value (PPV) of 85% for ruling-in NASH. In the pooled validation cohort (n=1,089), the diagnostic performance of the index was also good with AUROC=0.805 (95%CI 0.780-0.830), NPV of 93% for ruling-out NASH and PPV of 73% for ruling-in NASH. Subgroup analyses showed similar performance in patients with diabetes or subjects with normal serum transaminase levels. Interpretation: The acNASH index shows promising utility as a simple non-invasive biomarker for diagnosing NASH among adults with biopsy-proven NAFLD of different ethnicities from different countries. Funding: The National Natural Science Foundation of China (82070588), High Level Creative Talents from Department of Public Health in Zhejiang Province (S2032102600032) and Project of New Century 551 Talent Nurturing in Wenzhou. (c) 2021 The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Nonalcoholic steatohepatitis; primary care; screening; metabolic dysfunction-associated fatty liver; disease; nonalcoholic fatty liver disease; scoring system; FATTY LIVER-DISEASE; URINARY CREATININE; BIOMARKER PANEL; MUSCLE MASS; FIBROSIS; ASSOCIATION; MODEL; NASH